DETERMINAN KEJADIAN HIPERTENSI PADA USIA PRODUKTIF - Wahyuni, Maria Magdalena Dwi; Afriza, Renita; Fitri, Yenti; Yusfinaldi, Yusfinaldi; Mitra, Muhammad Ikhlas Iryadi (Ensiklopedia of Journal, 2024)
Abstract: Based on data obtained from the Sitinjak Health Center, the number of people with hypertension has increased in three consecutive years. In 2021, there were 144 people with hypertension, which then increased to 162 people in 2022. In 2023, the number of sufferers increased again to 176 people. Of the total 176 people with hypertension, the majority were adult women, with a total of 105 people, while 71 men were recorded. The purpose of the study was to determine the determinants of the incidence of hypertension in productive age. The study used a type of quantitative research with a cross sectional design. The research was conducted in July 2023 in the Sitinjak Health Center working area. The sample amounted to 51 people. The sampling technique used Accidental Sampling. The research instrument used a research questionnaire. Data analysis was done univariate and bivariate. The results showed that there was a relationship between physical activity (p value: 0.010) and eating habits (p value: 0.000) on the incidence of hypertension in productive age. It is recommended to the Puskesmas to further improve health services through health counseling, encourage routine control and conduct health counseling about changing good eating habits for people with hypertension so as to prevent and reduce the incidence of hypertension.Keywords: Physical Activity, Hypertension, Eating Habits, Health Center.